Fatalities due to dichloromethane in paint strippers: A continuing problem. Issue 8 (28th February 2013) - MacIsaac, Julia; Harrison, Robert; Krishnaswami, Janani; McNary, Jennifer; Suchard, Jeffrey; Boysen‐Osborn, Megan; Cierpich, Hank; Styles, Laura; Shusterman, Dennis
Abstract Background Exposure to dichloromethane (DCM or methylene chloride ‐ CH2Cl2) in paint strippers continues to be an avoidable source of morbidity and mortality. DCM has been under regulatory scrutiny by occupational and consumer product agencies since the identification of its carcinogenicity in the mid‐1980s. Methods We investigated two independent workplace incidents that resulted in three cases of DCM intoxication from paint stripper use. Results Each incident investigated resulted in a fatality. A third worker suffered obtundation requiring hospitalization and intubation. Conclusions The continued occurrence of fatalities and other serious injuries due to DCM‐containing paint strippers in the United States calls for a re‐evaluation of existing regulatory strategies. Am. J. Ind. Med. 56:907–910, 2013. © 2013 Wiley Periodicals, Inc.